Improving Student's Vocabulary Through the Duolingo Application for Seventh Grade at SMP Negeri 3 Lahewa - Libertina Lase; Kristof Martin Efori Telaumbanua; Yaredi Waruwu Telaumbanua; Riswan Zega Telaumbanua (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2025)
This study aims to improve students' vocabulary. Students still lack vocabulary, which prevents them from achieving the Minimum Mastery Criterion (KKM). The subjects of this study were 26 seventh-grade students at SMP Negeri 3 Lahewa. The method used was Classroom Action Research (CAR), which was conducted in two cycles. There are two cycles, and in the first cycle, many students were still unable to achieve the Minimum Mastery Criterion (KKM). The results showed a significant improvement in students' vocabulary, with the average score increasing from 50.38 (19.23%) in cycle I to 68.46 (88.46%) in cycle II. Additionally, student activity levels improve from 93.75% in cycle I to 100% in cycle II. This study concludes that the Duolingo app is effective in helping students improve their vocabulary and encouraging active participation in the learning process. Therefore, this study successfully improved students' vocabulary in nouns, verbs, adjectives, and adverbs using the Duolingo app. It is hoped that teachers can continue to apply methods that can improve students' vocabulary and creativity.